2020
DOI: 10.1074/jbc.ra119.011648
|View full text |Cite|
|
Sign up to set email alerts
|

DAPLE protein inhibits nucleotide exchange on Gαs and Gαq via the same motif that activates Gαi

Abstract: Besides being regulated by G-protein–coupled receptors, the activity of heterotrimeric G proteins is modulated by many cytoplasmic proteins. GIV/Girdin and DAPLE (Dvl-associating protein with a high frequency of leucine) are the best-characterized members of a group of cytoplasmic regulators that contain a Gα-binding and -activating (GBA) motif and whose dysregulation underlies human diseases, including cancer and birth defects. GBA motif–containing proteins were originally reported to modulate G proteins by b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 85 publications
(120 reference statements)
0
9
0
Order By: Relevance
“…Daple has been reported to both trigger Gα i protein activation through the Gα binding and activating (GBA) motif ( Aznar et al, 2015 ; Leyme et al, 2017 ; Aznar et al, 2018 ; Marivin et al, 2019 ; Marivin and Garcia-Marcos, 2019 ; Marivin et al, 2020 ) and interact with Dvl and PARD3 through a PDZ-binding motif (PBM; Fig. 5 A ; Oshita et al, 2003 ; Ishida-Takagishi et al, 2012 ; Ear et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Daple has been reported to both trigger Gα i protein activation through the Gα binding and activating (GBA) motif ( Aznar et al, 2015 ; Leyme et al, 2017 ; Aznar et al, 2018 ; Marivin et al, 2019 ; Marivin and Garcia-Marcos, 2019 ; Marivin et al, 2020 ) and interact with Dvl and PARD3 through a PDZ-binding motif (PBM; Fig. 5 A ; Oshita et al, 2003 ; Ishida-Takagishi et al, 2012 ; Ear et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…We also found that LOV2GIVe retains the same G-protein specificity as GIV. Much like GIV (Garcia-Marcos et al, 2010;Marivin et al, 2020), LOV2GIVe bound robustly only to members of the G i/o family among the 4 families of Gα proteins (G i/o , G s , G q/11 and G 12/13 ), and could discriminate within the G i/o family by binding to Gαi1, Gαi2 and Gαi3 but not to Gαo (Fig. 2B).…”
Section: Lov2give Binds and Activates G-proteins Efficiently In Vitromentioning
confidence: 98%
“…We also found that LOV2GIVe retains the same G-protein specificity as GIV. Much like GIV ( Garcia-Marcos et al, 2010 ; Marivin et al, 2020 ), LOV2GIVe bound robustly only to members of the G i/o family among the four families of Gα proteins (G i/o , G s , G q/11, and G 12/13 ), and could discriminate within the G i/o family by binding to Gαi1, Gαi2 and Gαi3 but not to Gαo ( Figure 2B ). Next, we assessed if LOV2GIVe can activate G-proteins in vitro, that is whether it retains GIV’s GEF activity.…”
Section: Resultsmentioning
confidence: 99%